2019
DOI: 10.1194/jlr.m082198
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of acid ceramidase (ASAH1) protects retinal cells (ARPE19) from oxidative stress

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly population. More than 80% of AMD cases are of the dry-AMD classification, which characteristically features geographic atrophy resulting from the loss of retinal pigment epithelial (RPE) cells (1, 2). Dry-AMD often converts to wet-AMD, which is visionthreatening. Accumulation of undigested cellular debris (e.g., drusen), oxidative stress, and subsequent death and degeneration of RPE cells are important contributors to AMD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 80 publications
(89 reference statements)
0
22
0
Order By: Relevance
“…Oxidative stress increases Cer levels and induces apoptosis in human RPE cells and this was replicated by using C2- and C6-Cer (Barak et al, 2001). Oxidative stress increases both Cer and hexosyl-Cer levels in ARPE-19 cells, a human RPE cell line, promoting cell death; this death is prevented by over-expression of acid ceramidase, which increases Sph levels but not those of S1P (Sugano et al, 2018). Interestingly, increased serum levels of hexosyl-Cer have been reported in patients with late stage AMD (Pujol-Lereis et al, 2018).…”
Section: Ceramide a Crucial Executioner In Retinal Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress increases Cer levels and induces apoptosis in human RPE cells and this was replicated by using C2- and C6-Cer (Barak et al, 2001). Oxidative stress increases both Cer and hexosyl-Cer levels in ARPE-19 cells, a human RPE cell line, promoting cell death; this death is prevented by over-expression of acid ceramidase, which increases Sph levels but not those of S1P (Sugano et al, 2018). Interestingly, increased serum levels of hexosyl-Cer have been reported in patients with late stage AMD (Pujol-Lereis et al, 2018).…”
Section: Ceramide a Crucial Executioner In Retinal Degenerationmentioning
confidence: 99%
“…Interestingly, increased serum levels of hexosyl-Cer have been reported in patients with late stage AMD (Pujol-Lereis et al, 2018). Noteworthy, oxidative stress leads to increased S1P levels in control RPE cells, which might reflect an attempt to counteract Cer action toward cell death (Sugano et al, 2018). Laser exposure, a frequent treatment for retina neovascularization, induces human RPE cell death concomitant with Cer overproduction (Barak et al, 2005).…”
Section: Ceramide a Crucial Executioner In Retinal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Cer plays a crucial role in light-induced degeneration of photoreceptor cells and were able to conclude that FTY720 prevents excess Cer formation during light exposure 22 . We have also shown in our in vitro studies that reduction of Cer by overexpression of acid Ceramidase (ASAH1), a lysosomal enzyme which degrades excess Cer, in retinal pigment epithelial (RPE) cells provides significant protection from oxidative stress-induced cell death, further highlighting the role of Cer in retinal degeneration 24 .…”
Section: Introductionmentioning
confidence: 63%
“…An age-dependent inhibition of ACDase leads to ceramide accumulation, an increase in oxidative stress, and the death of retinal cells and erythrocytes [ 27 , 28 ]. By contrast, it was reported that kidney cells collected from aged mice show an elevated expression of Asah1 mRNA compared to that of young mice [ 29 ].…”
Section: Characteristics and Regulatory Pathways Of Ceramidasesmentioning
confidence: 99%